ادارة الجودة الشاملة في المؤسسات الرياضية - شريف ، حمزة (Mohamed Boudiaf University of M'Sila, 2023)
الملخص : بالعربية : تشمل المطبوعة على عدة محاور، يتطرق بعض منها إلى المفاهيم الأساسية للجودة وإدارتها، من خلال تعريف الجودة وتحديد مختلف أبعادها ومحدداتها، والتعرف على مداخلها، ثم إستعراض مختلف مراحل تطور الجودة وأسباب الإهتمام بها، كما يتم عرض بعض رواد الجودة، و يعالج محور اخر من المطبوعة مفهوم إدارة الجودة الشاملة، والتفرقة بين مصطلح إدارة الجودة كوظيفة في المنظمة أو كوحدة إدارية، ويبين هذه المحور إدارة الجودة الشاملة كنظام إداري شامل ومفتوح، وتم تحديد مداخل إدارة الجودة الشاملة، أهميتها، أهدافها، عناصرها، كما يتم إبراز مبادئ وعناصر ومراحل تطبيق إدارة الجودة الشاملة في المؤسسات الرياضية ، مع الإشارة إلى تنظيم إدارة الجودة الشاملة في المنظمات، إستهدف محور اخر تسليط الضوء على المواصفة العالمية الإيزو 9000، تعريفها، تطورها، وكيفية الحصول على الشهادة، وكذلك تم التطرق إلى العديد من أنظمة الإيزو والأكثر إنتشارا عالميا. Searchlight in English The publication includes several axes, some of which address the basic concepts of quality and its management, by defining quality and identifying its various dimensions and determinants, and identifying its approaches, then reviewing the various stages of quality development and the reasons for interest in it, as well as presenting some quality pioneers. Another axis of the publication addresses the concept of total quality management, and the distinction between the term quality management as a function in the organization or as an administrative unit. This axis shows total quality management as a comprehensive and open administrative system, and the approaches to total quality management, its importance, objectives, and elements were identified. The principles, elements, and stages of applying total quality management in sports institutions are also highlighted, with reference to organizing total quality management in organizations. Another axis aims to shed light on the international standard ISO 9000, its definition, development, and how to obtain the certificate, as well as addressing many of the most widespread ISO systems globally.
Keywords: ادارة; الجودة الشاملة; ادارة الجودة الشاملة